Designing Randomised Trials in Health, Education and the Social Sciences - Torgerson, D. author. aut Link
XV, 210 p.
Keywords: The book focuses on the design of rigorous trials rather than their statistical underpinnings, with chapters on: pragmatic designs; placebo designs; preference approaches; unequal allocation; economics; analytical approaches; randomization methods. It also includes a detailed description of randomization procedures and different trial designs.